Solar dye degradation using TiO2 nanosheet based nanocomposite floating photocatalyst. (2021) - Nair, Abhinav K; Roy George, Deepak; Jos Baby, Nibin; Reji, Mathews; Joseph, Sebin
Abstract: Floating photocatalysts are viable options for the degradation of pollutants using solar radiation. The presence of photocatalyst floating on top of the water body can enable better exposure to Sunlight and better air contact for photo-degradation. Direct use of powder photocatalyst in water bodies is impracticable. In the present work, TiO2 nanosheets were immobilized in a cellulose acetate matrix and provided support using Ethylene Vinyl Acetate to develop a floating photocatalyst. The performance of the floating photocatalyst for degrading pollutants under solar radiation was evaluated using Congo red dye as a model pollutant. The TiO2 nanosheet based floating photocatalyst showed good performance in the degradation of Congo red dye. X-ray diffraction and Field emission scanning electron microscopy were used to characterize the photocatalyst.